Etnomatematika: Identifikasi Konsep Geometri pada Peralatan Nelayan Cumi-Cumi di Desa Ekor - Winda Syam Tonra; Soleman Saidi; Kusnadi Abd Muis; Dahlan Wahyudi; Wilda Syam Tonra (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2026)
This study aims to reveal the geometric concepts embedded in the squid fishermen’s equipment used in Ekor Village, North Maluku. A qualitative approach with an ethnographic method was employed because the study focused on the cultural practices of the fishing community related to the use of traditional fishing equipment. Data were collected through field observations, interviews, and documentation involving one fishing captain and three crew members who were directly engaged in squid fishing activities. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that various squid fishing tools contain identifiable geometric concepts. The fishing net reflects the concept of a square, while the arrangement of its mesh openings forms a square tessellation pattern, and the overall shape of the net resembles a truncated pyramid. The scoop net incorporates the concept of a circle in its frame, whereas its netting resembles a truncated cone. In addition, the basket used to store the catch exhibits the shape of a truncated cone. These findings demonstrate that mathematical concepts are not limited to formal educational settings but are also embedded in the fishing equipment used by coastal communities in their daily activities. This study contributes to the development of ethnomathematics research and provides implications for culturally responsive mathematics learning by utilizing squid fishing equipment as contextual learning resources in geometry instruction.